Local heating self-melting adhesive tape

Through multi-layer structure design and locally heated self-melt tape with optimized material formula, the problems of high-temperature start-up requirements, insufficient dynamic environmental performance, uneven thermal conductivity, weather resistance and service life in the existing technology are solved, and the rapid start-up of low temperature, high dynamic adaptability and excellent weather resistance are achieved, and are suitable for a wide range of industrial and outdoor applications.

CN119709039APending Publication Date: 2025-03-28福建友谊胶粘带集团有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411937070.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing locally heated self-melt tape has shortcomings in high-temperature starting requirements, insufficient dynamic environmental performance, uneven thermal conductivity, weather resistance and service life, which limits its application in low-temperature, high-temperature sensitive materials and high-dynamic stress environments.

Method used

The multi-layer structure design and optimized material formulation, including inner, intermediate and outer layers, were prepared by dynamic composite processes. The inner layer uses low melting point copolyester and tackifier for rapid bonding at low temperatures, the intermediate layer uses graphene modified nanosilicon to improve thermal conductivity and mechanical properties, and the outer layer is coated with dynamic reversible chemical bond materials to provide weather resistance and self-healing properties.

Benefits of technology

It realizes rapid self-fusion under low temperature conditions, is suitable for temperature range of -40℃ to 150℃ and dynamic vibration environments of 50-100Hz, significantly improves weather resistance and self-repair performance, and is suitable for a variety of industrial and outdoor application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709039A_ABST
    Figure CN119709039A_ABST
Patent Text Reader

Abstract

The invention relates to a local heating self-melting adhesive tape, in particular to a multi-layer structure adhesive tape which can be quickly self-melted under a low-temperature condition, is suitable for a dynamic environment and has excellent weather resistance. The adhesive tape consists of three parts, namely an inner layer, a middle layer and an outer layer, and is prepared by a dynamic compounding process. The inner layer is made of thermoplastic polyurethane, a block copolymer, low-melting-point copolyester and other materials, and can be melted at 40-60 DEG C to form strong adhesive force with a base material; graphene modified nano silicon and lubricating silicone oil which are arranged in an oriented manner are added into the middle layer, so that the thermal conductivity, the mechanical property and the dynamic adaptability of the adhesive tape are remarkably improved; and the outer layer is coated with a dynamic reversible chemical bond material, so that excellent anti-aging and self-repairing capabilities are achieved. The adhesive tape disclosed by the invention realizes function synergy of each layer through a multi-layer extrusion and electric field induction molding process, has the advantages of fast low-temperature starting, strong dynamic environment adaptability and good long-term weather resistance, and is suitable for scenes of electrical maintenance, pipeline sealing, industrial equipment repair and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesive tapes, and in particular relates to a locally heated self-melting adhesive tape. Background Art

[0002] Local heating self-melting tape is a functional tape that activates material melting or bonding through local heat. It is widely used in industries, electrical maintenance, automotive wiring harness repair, pipeline sealing and other fields. It achieves high-strength adhesion between materials through self-melting, which is especially important in emergency repairs and special environments. However, the existing local heating self-melting tape technology still has the following problems and limitations:

[0003] 1. High temperature start requirements

[0004] In the prior art, self-melting tapes usually need to be heated to a temperature above 120°C to achieve effective bonding of materials. This high temperature requirement places high demands on construction equipment, while increasing energy consumption and safety risks during the construction process. In particular, the applicability of the prior art is limited in the application scenarios of low-temperature or high-temperature sensitive materials (such as PVC and composite substrates).

[0005] 2. Insufficient performance in dynamic environments

[0006] Traditional self-melting tapes are mostly single-layer structures, which are prone to material fatigue, bonding failure or interlayer separation in high dynamic stress environments (such as continuous vibration, bending or stretching). This performance deficiency has limited its application in aerospace, automobiles and high-frequency vibration equipment.

[0007] 3. Uneven thermal conductivity

[0008] In the prior art, adhesive tapes with low thermal conductivity are prone to local overheating or cold spots during heating, affecting the uniformity and strength of bonding. In addition, due to uneven distribution of fillers or poor thermal conductivity of the substrate, the material is prone to deformation or performance degradation at high temperatures.

[0009] 4. Weather resistance and service life issues

[0010] Traditional tapes are prone to aging, cracking or failure when exposed to ultraviolet rays, humidity, heat or extreme climates for a long time. Especially in application scenarios such as outdoor equipment and electrical repair, the long-term stability of existing technologies cannot meet the needs. These problems increase the maintenance and replacement costs of products.

[0011] 5. Single-layer structure is not functional enough

[0012] Existing local heating self-melting tapes are usually designed as a single layer, which cannot meet multiple requirements such as adhesion, mechanical properties and weather resistance at the same time. The modification of a single layer of material often leads to performance compromises and is difficult to meet the requirements of multi-functional usage scenarios. Summary of the invention

[0013] The purpose of the present invention is: The present invention aims to provide a locally heated self-melting tape, which, through a multi-layer structure design and optimized material formulation, can quickly self-melt under low temperature conditions, is suitable for dynamic environments, and has excellent weather resistance and self-healing properties, thereby significantly improving its comprehensive performance and application range.

[0014] The technical solution adopted by the present invention is as follows:

[0015] A locally heated self-melting adhesive tape, the adhesive tape comprising an inner layer, a middle layer and an outer layer, and is prepared by a dynamic composite process;

[0016] Inner layer: mainly used to achieve rapid bonding with the substrate under local heating conditions;

[0017] Ingredients ratio:

[0018] Thermoplastic polyurethane: 30-40wt%;

[0019] Block copolymer: 20-30wt%;

[0020] Low melting point copolyester: 10-15wt%;

[0021] Acrylate-based tackifier: 5-10wt%;

[0022] Middle layer: mainly used to improve the mechanical properties and thermal conductivity of the tape;

[0023] Ingredients ratio:

[0024] Thermoplastic polyurethane: 25-35wt%;

[0025] Block copolymer: 15-25wt%;

[0026] Graphene modified nano-silicon: 5-8wt%;

[0027] Silicon powder: 1-2wt%;

[0028] Liquid silicone oil: 3-5wt%.

[0029] Outer layer: mainly used to provide weather resistance and anti-aging performance;

[0030] Ingredients ratio:

[0031] Two-component polyurethane prepolymer: 1-3wt%;

[0032] Dynamic reversible chemical bond materials: 1-3wt%;

[0033] The coating thickness is 10-50 μm; the inner layer, the middle layer and the outer layer are tightly combined through a dynamic die head superposition process, and the thickness deviation of each layer is controlled within ±5%.

[0034] The adhesive tape can be self-melted within 3-5 seconds under the condition of local heating to 40-60°C, and is suitable for a temperature range of -40°C to 150°C and a dynamic vibration environment of 50-100Hz.

[0035] The thermoplastic polyurethane has a hardness of 70A-90A, and the styrene content of the block copolymer is 30-40wt%.

[0036] The graphene-modified nano-silicon particles in the intermediate layer have a particle size of 10-100 nm and are evenly dispersed through high shear mixing.

[0037] A method for preparing the locally heated self-melting adhesive tape comprises the following steps:

[0038] Step 1. Dynamic step mixing:

[0039] a. Mix the thermoplastic polyurethane, block copolymer and low melting point copolyester at 60-70°C for 8-12 minutes;

[0040] b. Add acrylate-based tackifier at 80-90°C and continue mixing for 5-8 minutes.

[0041] Step 2. High shear dispersion:

[0042] The graphene-modified nano-silicon and silicon powder are uniformly dispersed in the matrix material by a high shear dispersion device at 50-60°C for 8-12 minutes;

[0043] Step 3. Extrusion and composite molding:

[0044] Use a multi-layer extrusion device to form an outer bonding layer, an intermediate reinforcing layer and an outer protective layer at 60-120°C; realize three-layer composite molding through a dynamic die head, and obtain a semi-finished tape after cooling to room temperature;

[0045] Step 4. Subsequent heat-light treatment:

[0046] a. Heat treatment at 70-80℃ for 20-40 minutes to release internal stress;

[0047] b. Apply a UV-curable self-healing coating on the surface and cure it by irradiating it with 365-400nm UV light for 5-15 seconds.

[0048] Wherein, the graphene-modified nano-silicon is subjected to coupling treatment at 50-70° C. for 15-30 minutes before extrusion to enhance the interface bonding force with the substrate.

[0049] The thickness of the inner layer is 0.1-0.5 mm, the thickness of the middle layer is 0.5-1.5 mm, and the thickness of the outer layer is 0.05-0.2 mm.

[0050] The main technical features of the present invention include low-temperature rapid start-up, multi-layer structure design, high dynamic environmental adaptability, and excellent weather resistance and self-repair performance. Its beneficial effects include:

[0051] 1. Low temperature quick start performance

[0052] The startup temperature of traditional self-melting tapes is usually above 120°C, and the high temperature requirement places high demands on equipment and operators. The inner layer (adhesive layer) of the present invention uses low melting point copolyester (LMP) and high-efficiency tackifiers to significantly reduce the self-melting startup temperature to 40-60°C. Acrylate-based tackifiers and bifunctional active polymer additives provide chemical and physical intercalation to enhance low-temperature bonding strength. This reduces the operating temperature, making it suitable for low-temperature or emergency repair scenarios, reducing safety hazards in high-temperature operations, and expanding the scope of application on low-temperature and high-temperature sensitive materials.

[0053] 2. Functional synergy of multi-layer structural design

[0054] Traditional tapes are mostly single-layer designs, which cannot take into account multiple performances. The present invention achieves functional separation and synergy through layered design, significantly improving the overall performance. The inner layer provides adhesion and flexibility, the middle layer enhances thermal conductivity and mechanical properties, and the outer layer achieves self-repair function through dynamic reversible chemical bonds. The three-layer structure is seamlessly combined through dynamic die composite technology. It improves bonding strength, thermal conductivity and durability, and meets complex and diverse application requirements (such as electrical repair and pipeline sealing).

[0055] 3. High dynamic environment adaptability

[0056] Ordinary self-melting tapes are prone to material fatigue or decreased bonding strength under dynamic conditions (such as vibration and bending). The intermediate layer of the present invention adopts a dynamic lubrication system (liquid silicone oil) and a high thermal conductivity two-dimensional network (oriented graphene) to enhance vibration resistance and bending resistance. The oriented arrangement of graphene sheets forms an efficient heat conduction channel, which significantly reduces local stress concentration. It can withstand dynamic vibrations of 50-100Hz and has a bending life of more than 10,000 times. It has long-term stability in high-dynamic scenarios such as industrial equipment, automotive wiring harnesses, and aerospace, reducing maintenance costs.

[0057] 4. Excellent weather resistance and self-repairing performance

[0058] Ordinary tapes are prone to aging, cracking and failure in long-term exposure environments, but the outer layer of the present invention is coated with a dynamic reversible chemical bond material (disulfide bond chemical network) to achieve self-repair of microcracks. UV curing technology forms a high-strength coating, which significantly improves resistance to UV aging and environmental corrosion. There is no obvious performance degradation after 2000 hours of outdoor UV exposure. It can provide long-term reliability and is suitable for long-term exposure application scenarios such as outdoor equipment repair and cable joint protection, reducing replacement frequency and maintenance costs.

[0059] 5. Significant improvement in thermal conductivity

[0060] The thermal conductivity of traditional adhesive tape is low, resulting in local overheating or incomplete melting. The graphene-modified nano-silicon of the present invention forms an efficient two-dimensional thermal conductive network through high shear dispersion and electric field orientation. The thermal conductivity of the middle layer is improved to ensure uniform temperature distribution during local heating. The thermal conductivity is increased by 50%-100%, ensuring a uniform and stable bonding process. It can eliminate local overheating or cold spots, optimize construction quality and effect, and is suitable for repair scenarios with high thermal conductivity requirements.

[0061] 6. Efficient preparation process

[0062] Traditional processes mostly rely on a single mixing or molding step, resulting in uneven distribution of components or insufficient interfacial bonding. The present invention uses dynamic step-by-step mixing and high shear dispersion technology to ensure uniform distribution of multiple components (such as fillers and additives). The extrusion molding process is combined with dynamic die head technology to achieve a high-precision three-layer composite structure. The dispersion uniformity and interlayer bonding strength are optimized. This improves production efficiency and reduces performance fluctuations or product defects caused by poor material dispersion. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 It is a schematic diagram of the process of the present invention. DETAILED DESCRIPTION

[0064] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0065] See also Figure 1 The present invention relates to a locally heated self-melting adhesive tape, in particular to a multi-layer structural adhesive tape which can self-melt quickly under low temperature conditions, is suitable for dynamic environments and has excellent weather resistance.

[0066] The locally heated self-melting adhesive tape of the present invention consists of three parts: an inner layer (adhesive layer), an intermediate layer (reinforcement layer) and an outer layer (protective layer), and is prepared by a dynamic composite process.

[0067] Inner layer (adhesive layer): The inner layer is used to melt and flow under local heating (40-60°C) conditions, form a close adhesion with the substrate, and have flexibility to adapt to the shape and dynamic changes of the substrate.

[0068] Formula and range:

[0069] Thermoplastic polyurethane (TPU): 30-40wt%, providing flexibility and low temperature adaptability, optional polyester TPU, polyether TPU or mixed TPU;

[0070] Block copolymer (SEBS): 20-30wt%, enhances bonding strength, styrene-ethylene / butylene-styrene;

[0071] Polyalkoxide block: 3-8wt%, to enhance flexibility through a dynamic molecular network, polyethylene glycol block (PEG), polypropylene glycol block (PPG) or polyethylene oxide-polypropylene oxide copolymer (PEO-PPO) can be selected;

[0072] Low melting point copolyester (LMP): 10-15wt%, used for low temperature startup and initial flow, ethylene glycol-terephthalate copolyester (PETG), adipic acid-butylene glycol copolyester (PBAT) or polycaprolactone (PCL) can be selected;

[0073] Acrylate-based tackifier: 5-10wt%, to enhance adhesion to low surface energy substrates, methacrylates, ethylhexyl acrylates (EHA) or styrene-modified acrylates may be selected;

[0074] Bifunctional active polymer additive: 3-5wt%, forming chemical intercalation between epoxy group and carboxyl group to improve adhesion stability, epoxy acrylate, polycarboxylate or multifunctional isocyanate modified materials can be selected.

[0075] Middle layer (reinforcement layer): The middle layer is used to improve the mechanical properties and thermal conductivity of the tape, adapt to the dynamic stress environment, and maintain the stability of the tape in high dynamic scenarios.

[0076] Formula and range:

[0077] Thermoplastic polyurethane (TPU): 25-35wt%, as the flexible matrix of the reinforcing layer, polyester TPU, polyether TPU or mixed TPU can be selected;

[0078] Block copolymer (SEBS): 15-25wt%, improves dynamic toughness, styrene-ethylene / butylene-styrene;

[0079] Graphene-modified nano-silicon: 5-8wt%, formed into a highly thermally conductive two-dimensional network through electric field-induced orientation, optionally reduced graphene oxide (rGO), graphene oxide (GO) or nitrogen-doped graphene;

[0080] Silicon powder: 1-2wt%, improve interlayer bonding strength, molten silicon powder or spherical silicon powder can be selected;

[0081] Liquid silicone oil: 3-5wt%, provides uniform lubrication to adapt to dynamic environments.

[0082] Outer layer (protective layer): The outer layer is used to provide weather resistance and anti-aging properties, and realize the self-repair function of microcracks through dynamic reversible chemical bonds.

[0083] Formula and range:

[0084] Two-component polyurethane prepolymer: 1-3wt%, providing surface protection, optional aromatic polyurethane prepolymer or aliphatic polyurethane prepolymer;

[0085] Dynamic reversible chemical bond material: 1-3wt%, used for self-repair of microcracks, optional disulfide bond chemical network, imide bond material or hydrogen bond network material.

[0086] In this example, the recipe selection is:

[0087] Thermoplastic polyurethane (TPU): polyester type TPU.

[0088] Low melting point copolyester: polycaprolactone (PCL).

[0089] Graphene: reduced graphene oxide (rGO).

[0090] Silicone oil: low viscosity silicone oil (100mPa·s).

[0091] Polyurethane prepolymer: aliphatic polyurethane.

[0092] Dynamic chemical bonds: disulfide chemical networks.

[0093] The coating thickness is 10-50μm.

[0094] The preparation process of the local heating self-melting tape is as follows:

[0095] Step 1. Dynamic step mixing

[0096] a. Matrix mixing: Add thermoplastic polyurethane (TPU), block copolymer (SEBS) and polyalkoxide block into an internal mixer at 60-70°C and mix for 8-12 minutes to form a uniform matrix.

[0097] Thermoplastic polyurethane (TPU) is in a partially softened state at 60-70°C, which enhances the fluidity of the matrix and makes it easier for other components to disperse evenly. The styrene hard segment in the block copolymer (SEBS) remains rigid at this temperature, while the rubber segment softens, promoting physical compatibility with TPU and enhancing the mixing effect. The dynamic molecular segments in the polyalkoxide block can form weak intermolecular forces within this temperature range, initially constructing a flexible network and improving the dynamic adaptability of the tape.

[0098] This step forms a matrix with good flexibility and dynamic properties, providing a uniform distribution basis for the subsequent addition of reinforcing components and fillers. Ensure that the matrix after mixing is uniform without obvious phase separation or particle deposition.

[0099] b. Adding reinforcing components: Add low melting point copolyester (LMP), acrylate-based tackifier and bifunctional active polymer additive at 80-90°C and continue mixing for 5-8 minutes.

[0100] Low melting point copolyester (LMP) completely melts at 80-90°C, distributes in the matrix, fills microscopic gaps, and reduces the overall startup temperature. The tackifier molecules in the acrylate-based tackifier diffuse at high temperatures, physically intercalate with polyurethane and block copolymers, and improve adhesion to low surface energy materials. The epoxy group and carboxyl group of the bifunctional active polymer additive are active under heating conditions, forming preliminary chemical bonds with other components, improving the bonding performance and chemical stability of the mixture.

[0101] This step ensures that the reinforcing components are evenly dispersed, significantly reducing the start-up temperature and improving the bonding performance. The overall cohesion and adhesion are enhanced by the introduction of intermolecular forces or chemical bonds.

[0102] c. Lubricant and filler dispersion:

[0103] Cool down to 50-60℃, add liquid silicone oil, graphene-modified nano-silicon and silicon powder, and mix them under high shear for 3-5 minutes to ensure that the filler is evenly dispersed.

[0104] Liquid silicone oil is evenly distributed in the matrix under the action of shear force and combines with the dynamic network to provide long-term lubrication and anti-friction performance. The modified graphene sheets in graphene-modified nano-silicon are evenly dispersed at a lower temperature, and the surface coupling agent further improves its interfacial bonding force with the matrix. Silicon micropowder reduces particle agglomeration through high shear action and enhances the interlayer bonding strength of the material.

[0105] This step ensures that the lubricant and filler are evenly distributed, forming a composite structure with lubrication and reinforcement effects, reducing micro defects and improving stability in dynamic scenarios.

[0106] Step 2. High Shear Dispersion

[0107] a. Graphene modification treatment: Add silane coupling agent to graphene at 50-70°C and perform coupling treatment for 15-30 minutes to enhance the interfacial bonding force with the matrix material.

[0108] One end of the silane molecule of the silane coupling agent is bonded to the graphene surface through a chemical bond, and the functional group at the other end interacts with the matrix material to improve the interfacial bonding strength. Temperature control ensures the best activity of graphene surface modification and avoids agglomeration or thermal decomposition.

[0109] This step significantly enhances the interfacial bonding between graphene and the matrix, and improves the mechanical strength and thermal conductivity of the composite material.

[0110] b. High shear mixing: At 50-60°C, the modified graphene is mixed with the matrix through a high shear device and sheared for 8-12 minutes to form a uniformly distributed lamellar structure.

[0111] The shearing action peels off the modified graphene sheets to form a uniformly distributed two-dimensional network. The mixing uniformity shear force avoids particle agglomeration and ensures the uniform distribution of thermal conductive fillers in the matrix.

[0112] This step builds an efficient thermal conductive network and improves the thermal conductivity and dynamic mechanical properties of the tape.

[0113] Step 3. Extrusion and composite molding

[0114] a. Multi-layer extrusion process: Use three-layer co-extrusion equipment to form the bonding layer, reinforcement layer and protective layer respectively at 60-120°C; apply an electric field of 0.1-1kV / m at the extrusion die head to orient the graphene sheets in the matrix to form a high thermal conductivity two-dimensional network.

[0115] Multi-layer co-extrusion allows each layer of material to converge at the die head through independent extrusion channels to form a layered structure. Electric field induction: The electric field drives the graphene sheets to align along the substrate to form a thermally conductive two-dimensional network.

[0116] This step forms a three-layer tape with a clear structure, improving the functionality of each layer and the overall performance. The thermal conductivity is optimized by aligning the graphene.

[0117] b. Dynamic die lamination: The three-layer structure is seamlessly superimposed through the dynamic die, and the semi-finished tape is obtained after cooling to room temperature.

[0118] The dynamic die head adjusts the flow rate of each layer in real time to avoid interface defects; the interlayer interface structure gradually solidifies during the cooling process, achieving seamless integration of the three-layer structure and ensuring interlayer strength and adhesion.

[0119] Step 4. Heat-light treatment

[0120] a. Heat treatment: Heat treat the tape at 70-80℃ for 20-40 minutes to release internal residual stress and improve interlayer bonding strength.

[0121] Heat treatment releases residual stress in the matrix and avoids micro cracks during cooling. Heat treatment enhances the diffusion effect of the matrix molecular chain and further improves the interlayer bonding strength. It improves the mechanical properties and overall stability of the tape.

[0122] b. UV curing: Apply a UV-curing self-healing coating on the surface of the tape and cure the coating by irradiating it with 365-400nm UV light for 5-15 seconds.

[0123] UV light triggers polymerization in the dynamic reversible chemical bond material to form a cross-linked network of the surface coating. The dynamic bonds form a reversible network that gives the coating the ability to repair microcracks. This provides excellent anti-aging properties and self-healing capabilities, enhancing the life of the tape in long-term exposure environments.

[0124] In this example, adhesive tapes were prepared and tested within the formulation and process ranges, and the results are summarized as follows:

[0125] Among them, test parameters and prerequisites

[0126] Self-starting performance:

[0127] Test method: Heat the tape sample locally to different temperatures and record the time required to achieve complete self-melting. Use a standard heater with a temperature control accuracy of ±1°C.

[0128] Standard judgment: self-fusion time ≤ 5 seconds is excellent, > 10 seconds is poor.

[0129] Dynamic adaptability:

[0130] Test method: Under dynamic stress environment (vibration frequency 50-100Hz), record the maximum frequency at which the sample bonding strength is maintained. Use a dynamic vibration platform, and the frequency error is ≤1Hz.

[0131] Standard judgment: The higher the maximum adaptation frequency, the better the performance.

[0132] Bending life:

[0133] Test method: Test the fracture life of the sample under dynamic bending on a cyclic bending test machine. The bending angle is ±90° and the frequency is 10Hz.

[0134] Standard judgment: bending life >10,000 times is excellent, <5,000 times is poor.

[0135] Weather resistance:

[0136] Test method: Perform UV irradiation test in a UV aging box and record the performance retention time. Irradiation intensity 1.0W / m 2 , wavelength 365nm.

[0137] Standard judgment: Weathering time ≥ 2,000 hours is excellent.

[0138] Bond Strength:

[0139] Test method: Test single lap shear strength according to ASTM D1002 standard and record the maximum bonding force. The bonding material is low surface energy plastic (PP).

[0140] Standard judgment: Bond strength ≥12N is excellent.

[0141] The following table shows the formula and preparation process of the 6 selected samples:

[0142]

[0143]

[0144] The following table shows the test results of 6 selected samples:

[0145]

[0146] The test results are analyzed as follows:

[0147] Self-melting start-up performance: The present invention can achieve rapid self-melting in 3-4.5 seconds within the range of 45-60°C, which is significantly better than the start-up time of 10-12 seconds and the high temperature requirement of 120-130°C of the control product.

[0148] Dynamic adaptability: The dynamic adaptability of the present invention reaches 75-100Hz, which is significantly better than the 50-60Hz of the control product, proving that it is more stable and reliable in dynamic environments such as vibration and bending.

[0149] Bending life: The present invention performs excellently in the bending life test, reaching 12,000-16,000 times, which is 2.5-3 times that of the control product.

[0150] Weather resistance: The weather resistance time of the present invention reaches 1,900-2,200 hours, while the control product is only 800-1,000 hours, indicating that the present invention has stronger UV resistance and aging resistance.

[0151] Bond strength: The present invention performs excellently in the bond strength test, reaching 13-17N, which is much higher than 7-8N of the control product.

[0152] in conclusion

[0153] Improved comprehensive performance: The present invention is significantly superior to existing mainstream products in terms of low-temperature starting performance, dynamic adaptability, weather resistance, bending life and bonding strength.

[0154] Expansion of applicable scenarios: The present invention is applicable to a wider range of environments, including low temperature conditions, high dynamic stress scenarios, and long-term exposure to ultraviolet rays.

[0155] Economical and safe: The present invention can be started quickly under low temperature conditions, which reduces energy consumption and potential safety hazards, while improving construction efficiency.

[0156] The multi-layer structure design and optimized formula of the present invention solve many defects of the prior art and provide an efficient and reliable solution for industrial applications.

[0157] The local heating self-melting tape of the present invention combines the characteristics of low-temperature rapid start-up, high dynamic adaptability and excellent weather resistance, and is suitable for a variety of industrial, construction and outdoor application scenarios. The following are specific usage methods and applicable fields:

[0158] Applicable scenarios

[0159] 1. Electrical maintenance

[0160] Application: Used for sealing and repairing cable joints to prevent the intrusion of water vapor and dust and improve insulation performance.

[0161] Specific usage: Wrap the tape around the cable connection. Use a handheld hot air gun to heat to 45-60°C to ensure that the tape is completely self-melted and adheres. After cooling, a firm sealing protective layer is formed.

[0162] 2. Pipeline sealing

[0163] Application: Repair cracks or joints in pipes and provide high pressure and corrosion resistant sealing solutions.

[0164] Specific usage: Clean the pipe surface to remove oil and impurities. Wrap the tape and stretch it slightly to enhance the fit. Use a heating tool to evenly heat the tape to form a sealing layer.

[0165] 3. Dynamic vibration equipment protection

[0166] Application: Used for mechanical parts that need to withstand vibration or dynamic stress (such as industrial equipment joints).

[0167] How to use: Wrap the tape around dynamic joints or areas prone to wear. After local heating, the tape adapts to dynamic stress through self-melting and graphene reinforcement layer.

[0168] 4. Aerospace applications

[0169] Application: Repairing aircraft cables, fuel pipes and other key components, resistant to high-frequency vibration and extreme temperatures.

[0170] Specific usage: Wrap the tape on the surface of the component. Use infrared heating equipment to heat the surface of the tape to ensure uniform bonding.

[0171] 5. Outdoor equipment repair

[0172] Application: Repair of communication base stations, outdoor cable connectors, and provide UV protection.

[0173] How to use: Wrap with tape and use handheld UV curing equipment to treat the surface coating. The self-healing coating provides long-term weather protection after curing.

[0174] Practical advantages

[0175] Quick repair: No complicated tools are required under on-site conditions, and quick repair can be achieved by only local heating, which is suitable for emergency repair scenarios.

[0176] Low temperature applicability: Able to maintain stable performance in the range of -40℃ to 150℃, suitable for applications in extreme environments.

[0177] Dynamic environment adaptability: The tape can withstand vibrations up to 100Hz and is suitable for dynamic sealing repairs in industrial machinery and transportation equipment.

[0178] Long-term weather resistance: UV-cured coating ensures a service life of more than 2,000 hours in outdoor environments, suitable for long-term exposure scenarios.

[0179] Multi-substrate compatibility: Good adhesion to metals, plastics (such as PP, PVC), and composite materials.

[0180] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A local heating self-melting tape, characterized in that: The adhesive tape comprises an inner layer, a middle layer and an outer layer, and is prepared by a dynamic composite process; Inner layer: mainly used to achieve rapid bonding with the substrate under local heating conditions; Ingredients ratio: Thermoplastic polyurethane: 30-40wt%; Block copolymer: 20-30wt%; Low melting point copolyester: 10-15wt%; Acrylate-based tackifier: 5-10wt%; Middle layer: mainly used to improve the mechanical properties and thermal conductivity of the tape; Ingredients ratio: Thermoplastic polyurethane: 25-35wt%; Block copolymer: 15-25wt%; Graphene modified nano silicon: 5-8wt%; Silicon powder: 1-2wt%; Liquid silicone oil: 3-5wt%. Outer layer: mainly used to provide weather resistance and anti-aging performance; Ingredients ratio: Two-component polyurethane prepolymer: 1-3wt%; Dynamic reversible chemical bond materials: 1-3wt%; The coating thickness is 10-50 μm; the inner layer, the middle layer and the outer layer are tightly combined through a dynamic die head superposition process, and the thickness deviation of each layer is controlled within ±5%.

2. The local heating self-melting adhesive tape according to claim 1, characterized in that: The adhesive tape can complete self-melting within 3-5 seconds under the condition of local heating to 40-60° C., and is suitable for a temperature range of -40° C. to 150° C. and a dynamic vibration environment of 50-100 Hz.

3. The local heating self-melting adhesive tape according to claim 1, characterized in that: The thermoplastic polyurethane has a hardness of 70A-90A, and the styrene content of the block copolymer is 30-40wt%.

4. The local heating self-melting adhesive tape according to claim 1, characterized in that: The graphene-modified nano-silicon particles in the intermediate layer have a particle size of 10-100 nm and are evenly dispersed through high shear mixing.

5. A method for preparing the locally heated self-melting adhesive tape according to claim 1, characterized in that: The following steps are involved: Step 1. Dynamic step mixing: a. Mix the thermoplastic polyurethane, block copolymer and low melting point copolyester at 60-70°C for 8-12 minutes; b. Add acrylate-based tackifier at 80-90°C and continue mixing for 5-8 minutes. Step 2. High shear dispersion: The graphene-modified nano-silicon and silicon powder are uniformly dispersed in the matrix material by a high shear dispersion device at 50-60°C for 8-12 minutes; Step 3. Extrusion and composite molding: Use a multi-layer extrusion device to form an outer bonding layer, an intermediate reinforcing layer and an outer protective layer at 60-120°C; realize three-layer composite molding through a dynamic die head, and obtain a semi-finished tape after cooling to room temperature; Step 4. Subsequent heat-light treatment: a. Heat treatment at 70-80℃ for 20-40 minutes to release internal stress; b. Apply a UV-curable self-healing coating on the surface and cure it by irradiating it with 365-400nm UV light for 5-15 seconds.

6. The preparation method according to claim 5, characterized in that: The graphene-modified nano-silicon is subjected to coupling treatment at 50-70° C. for 15-30 minutes before extrusion to enhance the interface bonding force with the substrate.

7. The local heating self-melting adhesive tape according to claim 1, characterized in that: The thickness of the inner layer is 0.1-0.5 mm, the thickness of the middle layer is 0.5-1.5 mm, and the thickness of the outer layer is 0.05-0.2 mm.